Teknik Editing Pada Film Rectoverso Dalam Mewujudkan Cerita - Ali, Moh. Mahrush; Sugihartono, Ranang Agung (Capture : Jurnal Seni Media Rekam, 2015)
This study aims to determine the editing technique that is applied to the Rectoverso film and to know how editing can form storytelling in the Rectoverso film. The study used descriptive qualitative approach. Data collection used interviews, observation, and literatures. Data analysis was performed based on the theories on Miles and Huberman, namely data reduction, data presentation, drawing conclusions, and verification. Type of editing applied in the film Rectoverso is continuity editing. This type of editing to ensure the achievement of sustainability of a series of stories in the scene of action. There are seven techniques and processes used to achieve the editing, namely Rules 1800, Shot/Reverse-shot, Establishing/reestablishing shot, eye line match, cutting point of view, cut-in, and match on action. The conclusions of the study that the use of continuity editing can form storytelling and supporting each scene in the movie. The splicing shot and scene shows the implicit message in it. Overall the Rectoverso film uses cross-cutting techniques or parallel editing. If the pattern is associated with the development of the story, then the movie Rectoverso uses three stages, namely, the stage of the beginning, middle, and closing. The goal is that the bond of causality (cause and effect) will be maintained because of the unity and development of the story is also determined by them. So, editing as one element in the Rectoverso film can also form the storytelling.Keywords: editing, Rectoverso, film, and story